Co-Designing Evidence-Based Videos in Health Care: A Case Exemplar of Developing Creative Knowledge Translation "Evidence-Experience" Resources. (16th July 2021) - Archibald, Mandy; Ambagtsheer, Rachel; Lawless, Michael T.; Thompson, Mark O.; Shultz, Timothy; Chehade, Mellick J.; Whiteway, Lyn; Sheppard, Anna; Plaza, Maria Pinero-de; Kitson, Alison L.
Objective: Well-designed evidence-based resources that reflect participant experiences and priorities are imperative for informed consumer health decision-making and to combat the pervasive health misinformation existing today. Qualitative research data can inform the development of such resources, but the process of reconciling qualitative research data with other sources of evidence through co-design processes is not well described in the literature. In response to the need for such evidence-based materials and corresponding methodological guidance, we co-designed a series of video resources through transdisciplinary and community partnership. In this manuscript, we provide methodological insight into the process of collaborative co-design to improve the utilization of qualitative research evidence into evidence-based resources for the public. Methods: Following from a large qualitative research study, we engaged in a collaborative and creative co-design process involving a multi-stakeholder advisory group guided by Boyd's co-design framework. We explicate this process, drawing from a case exemplar of transdisciplinary frailty research. Results: We utilized thematic qualitative data to co-produce: (i) an animation, (ii) a documentary-style video, (iii) a video vignette with key messages embedded in narratives of older adults, and (iv) a key-message video delivered by academic health researchers and clinicians. Discussion: The integration of experiential evidence of health care consumers with other sources of research evidence through co-design is an epistemological and procedural challenge with potential to improve public awareness, knowledge, and to support evidence-based decision making.